ADIWIYATA: Membangun Kepedulian dan Budaya LingkunganWarga Sekolah (Studi Kasus: SMPN 2 Gurah Kediri, Jawa Timur) - Nurul Jannah (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2019)
Environmental education in schools is the application of education which includes knowledge, awarenessand action. Environmental education applied by the Ministry of Environment and Forestry (KLHK) is theAdiwiyata Program. This program has the potential to raise school community awareness of theenvironment. This study aims to analyze the role of Adiwiyata in building environmental awareness andculture of school residents. This research uses descriptive qualitative methods and uses participatory datacollection techniques, interviews and documentation. The results of the study showed that the Adiwiyataprogram contributed positively to school achievement in the environmental field. SMPN 2 Gurah, Kediri isa favorite school because it has a high concern, creativity and school innovation in the field of environmentis very varied such as handmade batik with natural dyes, the development of local products such as passionfruit syrup, passion fruits and passion fruit preserves, and various waste recycling products to producehigh economic value. Schools that are able to make good use of all available spaces, both indoors andoutdoors for environmental learning while being able to involve the active participation of all schoolmembers will be better able to build schools that are environmentally friendly and cultured.